Climate Change, its History and Features in Contemporary Times - Samed, Mammadov Asgar; Yashar, Calalova Vafa (European Journal of Applied Sciences, 2022)
The effects of global climate change are increasing the economic tension as times go on. Thus, how long the inverse relationship between contemporary global warming and productivity will continue is often discussed among researchers and, unfortunately, remains unanswered. This article answers some of these and many related questions. Thus, it proposes a new model and forecasting methodology that explains the causes of climate changes. The forecasting methodology is tested for the temperature and the precipitation in Azerbaijan on the base of observational data. The conducted researches give reason to say that the forecast payment meets the requirements.